Emotion trajectories in smartphone use: Towards recognizing emotion regulation in-the-wild. Issue 166 (October 2022) - Tag, Benjamin; Sarsenbayeva, Zhanna; Cox, Anna L.; Wadley, Greg; Goncalves, Jorge; Kostakos, Vassilis
Highlights: A novel bottom-up approach to detect patterns of emotional change in smartphone usage data. Detection of non-random emotion trajectories in naturalistic settings Quantification and classification of the impact of distinct smartphone usage patterns on emotional trajectories of smartphone users Detailed reference to theory of Digital Emotion Regulation and Psychology of emotion regulation Abstract: Emotion has long been acknowledged as an important part of technology user experience. More recently, research has begun to catalogue ways in which people use technology to manage and shape emotion. These have been characterised as emerging digital forms of a category of behaviour known to psychologists as emotion regulation. Since digital emotion regulation may impact wellbeing, it is important to explore ways of studying it; however most studies to date have used self-report data and it remains unknown whether this behaviour can be studied objectively. To address this gap, we present findings from a field study that measured how joy unfolds during everyday smartphone use. We built a custom Android application that uses the front-facing camera to register emotions from facial features of 20 individuals, collected over 14 days. Our analysis of 266, 002 observations yielded striking non-random patterns, which we analyse as potential indicators of digital emotion regulation. This study is an important first step towards assessing how digital emotion regulation unfolds in naturalistic settings. Our findings have implications for the design of technology and in particular, interventions for psychological wellbeing.